Mycosynthesis of ZnO-NPs using Phoma sp. RDSE17 endophytic fungal extract and their in vitro antibacterial and wound healing applications - Prabhu Raju; Surendirakumar Kannaiah; Wairokpam Sanahal Devi; Kistu Singh Nongthombam; Sathish Muthukrishnan (Discover Chemistry)
Abstract The green synthesis of nanoparticles using natural reductants and stabilizers has gained popularity due to its biocompatibility, low cost, and broad range of biological applications. Microbial infections pose a significant challenge to wound healing and public health management. The prolonged use of antibiotics for treating infections and managing wounds can lead to the emergence of antibiotic-resistant pathogens. Zinc oxide nanoparticles (ZnO-NPs) offer considerable potential as therapeutic agents. This study aims to synthesize ZnO-NPs using Phoma sp. RDSE17 (PH), an endophytic fungus found on the roots of indigenous pigmented rice (Oryza sativa cv.). The physicochemical characteristics of the synthesized ZnO-NPs were analyzed using various techniques, including UV-Vis spectroscopy, X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), Field emission scanning electron microscopy (FE-SEM), energy-dispersive X-ray spectroscopy (EDAX), and zeta potential measurements. The characterization results confirmed the successful fabrication of bioactive ZnO-NPs with multifunctional properties. Antibacterial studies demonstrated significant reductions in bacterial growth and zones of inhibition against E. coli and B. subtilis. In the wound scratch assay, cells treated with ZnO-NPs exhibited enhanced cell regeneration and migration capabilities. Overall, this research indicates that fungal extract-mediated ZnO-NPs hold promise as effective therapeutics for antimicrobial and wound healing applications. Graphical abstract